Integrating Parasitoid Olfactory Conditioning in Augmentative Biological Control: Potential Impact, Possibilities, and Challenges - Kruidhof, H. Marjolein; Kostenko, Olga; Smid, Hans M.; Vet, Louise E. M. (Frontiers in Ecology and Evolution, 2019)
Despite of the vast body of theoretical and empirical literature dealing with parasitoid learning, this knowledge has thus far rarely been exploited for manipulating the efficacy of augmentative biological pest control. This may be due to the fact that most studies on learning behavior were performed under laboratory conditions, whereas field trials remain scarce. However, the few studies that did investigate parasitoid foraging success under (semi-)field conditions show strong learning effects. Using so-called ‘parasitoid olfactory conditioning’ (POC), parasitoids can be trained to become more efficient in the different phases involved in the process of host searching and host acceptance. POC can thus result in a ‘foraging efficacy gain’, defined as the difference between the number of naive and conditioned parasitoids that need to be released to reach a certain parasitization level of the target-pest in the crop environment. This ‘gain’ increases with an improved parasitoid learning ability and depends on the interplay between the parasitoid, crop, target-pest species and parasitoid rearing method. Moreover, the ‘foraging efficacy gain’ depends on the technical implementation of POC, as this will determine the strength, duration and stability of the learning-induced behavioral change. In this perspective paper we will discuss a) the conditions that can enhance the ‘foraging efficacy gain’, b) the possible approaches to implementation of POC and their costs and benefits, and c) a stepwise approach to develop appropriate POC methods for the optimization of biological pest control.